Acute effects of myofascial release exercise periods on circulatory parameters in young archers - Pancar, Z.; Alincak, F. (The Eurasia Proceedings of Health, Environment and Life Sciences, 2023)
The aim of this study was to investigate the acute effects of different myofascial release exercise durations on heart rate, saturation and blood pressure values in young archers. For this purpose, a total of 12 young athletes aged 16-18 years were included in the study. Myofascial release exercises using foam rollers were applied to the participants on different days. The inclusion criteria were determined as being healthy, not having a chronic disease, not having any medication used continuously and being interested in active archery sport. Control (T1), experimental (T2), and experimental (T3) foam rollers for 30 seconds and 60 seconds, respectively, were applied to the young archers on different days and heart rate, SpO2 levels and blood pressure values were measured after the applications. SPSS 22.0 programme was used to analyse the data obtained. One-way analysis of variance and LSD tests for repeated measures were performed to determine the difference between the groups of the application results. As a result of the analysis, no statistical significance was found in the saturation values, diastolic and systolic blood pressure values of the groups (p>0.05). There was statistical significance between T1 and T3 groups in the heart rate in favour of T3 (p<0.05). Myofascial release exercises affected the heart rate in terms of the parameters evaluated in long-term applications. It can be said that this change is a result of the energy and effort expended.